Financial Performance and Managerial Ownership on Financial Distress: Evidence from Indonesian Consumer Non-Cyclicals Sector - Muzrina, Rina; Anisa, Anisa (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to analyze the influence of financial performance, and managerial ownership on financial distress. The sample used was 15 companies in the Consumer Non Cyclicals sector listed on the Indonesia Stock Exchange during the period from 2019 to 2023 using purposive sampling techniques. The data used in this study is secondary data in the form of financial statements from each company that is used as a research sample. Analysis of research results using the help of Eviews software 13. The results of the study show that the Financial Performance proxied by Return on Asset partially affects Financial Distress. Financial Performance proxied by Return on Equity partially affects Financial Distress. Managerial ownership partially affects Financial Distress.